Antibiotic resistance genes and taxa analysis from mat and planktonic microbiomes of Antarctic perennial ice-covered Lake Fryxell and Lake Bonney. Issue 6 (December 2022) - Tallada, Sheetal; Hall, Grant; Barich, Daniel; Morgan-Kiss, Rachael M.; Slonczewski, Joan L.
Abstract: The perennial ice-covered lakes of the Antarctic McMurdo Dry Valleys harbour oligotrophic microbial communities that are separated geographically from other aquatic systems. Their microbiomes include planktonic microbes as well as lift-off mat communities that emerge from the ice. We used the ShortBRED protein family profiler to quantify the antibiotic resistance genes (ARGs) from metagenomes of lift-off mats emerging from ice and from filtered water samples of Lake Fryxell and Lake Bonney. The overall proportion of ARG hits was similar to that found in temperate-zone rural ponds with moderate human inputs. Specific ARGs showed distinct distributions for the two lakes and for mat vs planktonic sources. Metagenomic taxa distributions showed that mat phototrophs consisted mainly of cyanobacteria or Betaproteobacteria, whereas the water column phototrophs were mainly protists. An enrichment culture of the Betaproteobacterium Rhodoferax antarcticus from a Lake Fryxell mat sample showed an unusual mat-forming phenotype not previously reported for this species. Its genome showed no ARGs associated with Betaproteobacteria but had ARGs consistent with a minor Pseudomonas component. The Antarctic lake mats and water showed specific ARGs distinctive to the mat and water sources, but overall ARG levels were similar to those of temperate water bodies with moderate human inputs.